Extra-Axial Hematoma and Trimethoprim-Sulfamethoxazole Induced Aplastic Anemia: The Role of Hematological Diseases in Subdural and Epidural Hemorrhage - Richard P. Menger; Rimal H. Dossani; Jai Deep Thakur; Frank Farokhi; Kevin Morrow; Bharat Guthikonda (Case Reports in Hematology)
Objective and Importance. To illustrate the development of spontaneous subdural hematoma secondary to aplastic anemia resulting from the administration of trimethoprim-sulfamethoxazole. This is the first report of trimethoprim-sulfamethoxazole potentiating coagulopathy leading to any form of intracranial hematoma. Clinical Presentation. A 62-year-old female developed a bone marrow biopsy confirmed diagnosis of aplastic anemia secondary to administration of trimethoprim-sulfamethoxazole following a canine bite. She then developed a course of waxing and waning mental status combined with headache and balance related falls. CT imaging of the head illustrated a 3.7 cm × 6.6 mm left frontal subdural hematoma combined with a 7.0 mm × 1.7 cm left temporal epidural hematoma. Conclusion. Aplastic anemia is a rare complication of the administration of trimethoprim-sulfamethoxazole. Thrombocytopenia, regardless of cause, is a risk factor for the development of spontaneous subdural hematoma. Given the lack of a significant traumatic mechanism, this subset of subdural hematoma is more suitable to conservative management.